Produção animal, valor nutricional e aspectos morfológicos de braquiárias - Faria Filho, Edmir Marques (2012)
With the intensification of the agricultural sector, the need to develop new cultivars of tropical forage increases, which have better yield capacity and nutritional quality that suits Brazil s soil and climate conditions. The purpose of this study was to evaluate livestock, nutritional and morphological aspects of the Brachiaria hybrid cv. Mulato II and Brachiaria brizantha cv. Piata. The experiment was conducted on the Capim Branco Farm in Uberlândia Federal University. The experimental design used for the evaluation was done in randomized blocks (DRB). For the forages evaluation it was used a split-plot in time system. It was admitted two treatments - the cultivar Mulato II and Piata. We have evaluated the tiller density, leaf proportion, stem and dead material, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin content, in vitro degradability of dry matter (IVDDM), weight gain and average grazing pressure. The Cultivar Mulato II had greater (p<0.05) tiller density and leaf: stem in relation to Piata. Regarding the FDA, FDN and lignin content, the Piata was significantly (p<0.05) superior than cultivar Mulato II. As for the PB content and DIVMS, the Cultivar Mulato II showed superiority (p<0.05) compared to Piata. There was no significant difference (p>0.05) among cultivars in relation to the average grazing pressure, however, the weight gain was higher (p<0.05) to the animals that underwent the cultivar Mulato II.